Pronator Quadratus to Extensor Carpi Radialis Brevis Nerve Transfer in C5–C7 or C5–C8 Brachial Plexus Injuries for Independent Wrist Extension - Bhatia, Anil; Salama, Mahmoud (Indian Journal of Plastic Surgery, 2020)
Background Patients with lesions affecting C7 and C8 roots (in addition to C56) demonstrate loss of independent wrist dorsiflexion in addition to loss of shoulder abduction and elbow flexion. Traditionally, this deficit has been addressed using tendon transfers after useful function at the shoulder and elbow has been restored by primary nerve surgery. Confidence with nerve transfer techniques has prompted attempts to replace this method by incorporating procedures for wrist dorsiflexion in the primary operation itself.Aim The objective of this study was to report the results of pronator quadratus motor branch transfers to the extensor carpi radialis brevis motor branch to reconstruct wrist extension in C5–C8 root lesions of the brachial plexus.Patients and Methods Twenty-three patients, average age 30 years, with C5–8 root injuries underwent operations an average of 4.7 months after their accident. Extrinsic extension of the fingers and thumb was weak or absent in two cases while the remaining 18 patients could open their hand actively. The patients lacked independent wrist extension when they were examined with the fingers flexed as the compensatory action of the extrinsic finger extensors was removed. The average follow-up was 21 months postoperative with the minimal follow-up period was at least 12 months.Results Successful reinnervations of the extensor carpi radialis brevis (ECRB) were demonstrated in all patients. In 17 patients, wrist extension scored M4, and in 3 patients it scored M3.Conclusions The pronator quadratus (PQ) to ECRB nerve transfer in C5–C7 or C5–C8 brachial plexus injuries for independent wrist extension reconstruction gives consistently good results with minimal donor morbidity.
Keywords: pronator quadratus; nerve transfer; brachial plexus injuries; wrist extension reconstruction